Risk factors for development of phthisis bulbi in patients with posttraumatic ciliochoroidal detachment (Ukrainian Journal of Ophthalmology, 2026)
Background: Ciliochoroidal detachment (CCD) is one of the most severe traumatic ocular injuries that aggravates the course of post-traumatic process, usually results in phthisis bulbi and eye destruction, and is found in 9.0% to 30.8% of ocular trauma patients.Purpose: To determine the risk factors for the development of phthisis bulbi in severe ocular trauma patients with CCD based on the analysis of clinical course and treatment outcomes.Materials and Methods: We retrospectively reviewed the charts of 77 patients (77 eyes) with severe ocular trauma complicated by CCD who underwent treatment at the Filatov Institute during 2013 to 2015. The Aviso Ultrasound Biomicroscopy Unit (Quantel Medical, France) with 20-MHz and 50-MHz short focus probes had been used to evaluate the position of the ciliary body and the height of the detachment.Results: Phthisis bulbi was found to develop in 80% of patients with annular CCD, in 45.0% of patients with penetrating corneal and scleral injuries complicated by retinal detachment, and in 27.5% of patients with ocular contusion followed by rupture of ocular tunics and retinal detachment.Conclusion: Extent of CCD and specific types of ocular injury (a penetrating corneoscleral injury complicated by retinal detachment as well as an ocular contusion with rupture of the ocular tunics) are the main risk factors for the development of phthisis bulbi in severe ocular trauma patients with CCD.
Keywords: ocular trauma; ciliochoroidal detachment; risk factors; phthisis bulbi